Engineered bacteria as drug delivery vehicles: Principles and prospects - Yuxi Zhou; Yong Han (Engineering Microbiology, 2022)
The development of drug delivery vehicles is in significant demand in the context of precision medicine. With the development of synthetic biology, the use of genetically engineered bacteria as drug delivery vectors has attracted more and more attention. Herein, we reviewed the research advances in bioengineered bacteria as drug carriers, with emphasis on the synthetic biology strategies for modifying these bacteria, including the targeted realization method of engineered bacteria, the designing scheme of genetic circuits, and the release pathways of therapeutic compounds. Based on this, the essential components, design principles, and health concerns of engineering bacteria as drug carriers and the development prospects in this field have been discussed.